Prevalence of human papilloma virus genotypes 16, 18 in women with abnormal cervical cytology smears (abnormal Pap smear) attending Erbil Maternity Teaching Hospital - Mstafa, Razhan Nazhad; Jawad, Aryiana Khalis (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Cervical cancer is the fourth most common cancer among women. Carcinogenic Human Papilloma Virus (HPV) infection is the major etiological agent for cervical cancer, of which70% are caused by HPV-16 and HPV-18 genotype infection. This study aimed to detect high risk HPV (16,18) in women with different abnormalities in pap smear to allow subsequent more accurate management of the cases and provide information that assists in future development of guidelines in our hospital. Methods: We performed a cross-sectional study on 100 ladies with an abnormal pap smear. Subjects were interviewed and underwent cervical testing with broom using liquid based samples to confirm the cytological abnormality and test for HPV genotypes 16 and 18 using Polymerase Chain Reaction (PCR). Then, colposcopy referral was done according to local protocols. Results: The median age of the subjects was 34. The prevalence of HPV genotypes 16,18 in the whole studied sample was 36%. Various studied risk factors showed significant association with abnormal pap smear and positive HPV genotypes 16,18, including the number of partners, increasing parity, age at first pregnancy, and smoking. Data were analyzed by the statistical package for the social sciences (version 23). Conclusion: The prevalence of HPV 16,18 was 36% in the sample, with the highest proportion being among those with high-grade lesions. Those using natural methods of contraception had higher rates of infection in comparison with other methods.